2023
DOI: 10.3390/plants12040885
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Applied via Fertilizer Affects Plant Nutrition and Coffee Quality

Abstract: The present study had the objective to evaluate the effect of blends of KCl and K2SO4 fertilizers and their influence on the yield and the nutritional state of coffee plants, as well as on the chemical composition and quality of the coffee beverage. The experimental design was in randomized blocks with four repetitions and six treatments (T1: 100% KCl; T2: 75% KCl + 25% K2SO4; T3: 50% KCl + 50% K2SO4; T4: 25% KCl + 75% K2SO4; T5: 100% K2SO4; and a control, without application of K). The following analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Those results are indicating that for coffee the ideal Clconcentration on the soil should be below 30 mg. L -1 . In Coffee in Brazil Santos et al [20], found a significant difference in the Clcontent in the soil, the treatments with 100% K + applied as MOP had an average Clcontent in the soil in the first 20 cm of the depth of 130 kg.ha -1 (approx. 65 mg.L -1 of Cl -), while the treatment without Clwith 100% K + applied as SOP had a significantly lower Clcontent in the soil at the same depth equivalent to 50 kg .ha -1 (approx.…”
Section: Clon the Soilmentioning
confidence: 93%
See 3 more Smart Citations
“…Those results are indicating that for coffee the ideal Clconcentration on the soil should be below 30 mg. L -1 . In Coffee in Brazil Santos et al [20], found a significant difference in the Clcontent in the soil, the treatments with 100% K + applied as MOP had an average Clcontent in the soil in the first 20 cm of the depth of 130 kg.ha -1 (approx. 65 mg.L -1 of Cl -), while the treatment without Clwith 100% K + applied as SOP had a significantly lower Clcontent in the soil at the same depth equivalent to 50 kg .ha -1 (approx.…”
Section: Clon the Soilmentioning
confidence: 93%
“…Excess supply and uptake of Clin plants is a serious problem, mainly in crops that grow on salt-affected soils [1,19]. Recently Santos et al [20] demonstrate the negative effect of the chloride applied via fertilizers in coffee with respect to the productivity and coffee cup quality in the Minas Gerais state of Brazil, but no references are available regarding the effects of high Clsupplies on nitrogen use efficiency (NUE) in coffee growing under rainfed conditions. Hence, this research aimed to evaluate the influence of Clapplied at rates of a macronutrient on coffee on NUE in coffee.…”
Section: Of 16mentioning
confidence: 99%
See 2 more Smart Citations
“…Excess supply and uptake of Cl − in plants is a serious problem, mainly in crops that grow on salt-affected soils [ 1 , 20 ]. Recently, Santos et al [ 21 ] demonstrated the negative effect of chloride applied via fertilizers in coffee with respect to productivity and coffee cup quality in the Minas Gerais state of Brazil, but no references are available regarding the effects of high Cl − supplies on nitrogen use efficiency (NUE) in coffee growing under rainfed conditions. Hence, this research aimed to evaluate the influence of Cl − applied at rates as a macronutrient for coffee regarding growth, productivity, nutrient uptake, and NUE in coffee.…”
Section: Introductionmentioning
confidence: 99%